Saved by De-epithelialization. Issue 9 (September 2015) - Singh, Mansher; Carty, Matthew; Nuutila, Kristo; Ricci, Joseph A.; Caterson, Edward J.; Caterson, Stephanie A.
<x xml:space="preserve">Abstract</x> Background: Wound re-epithelialization has been traditionally described to occur from the dermal appendages of the wound edges. As such, the role of the dermal wound bed in re-epithelialization has been questioned. In a patient undergoing breast reconstruction with free tissue transfer, the buried portions of the free flap skin paddle could be either de-epithelialized or deskinned. In case of mastectomy skin flap loss, the role of de-epithelialized skin in wound healing has not been described before. Methods: We report a patient with bilateral mastectomies and bilateral deep inferior epigastric perforator flaps whose postoperative course was complicated by bilateral full-thickness mastectomy skin flap loss. Multiple debridements of nonviable skin resulted in exposure of previously buried de-epithelialized skin paddle of the deep inferior epigastric perforator flap. Results: Our study demonstrates self re-epithelialization of the dermal wound bed from the dermal appendages. We noticed multiple noncontiguous neoepidermal islands in the dermal wound bed, which did not communicate with the wound edges. Conclusions: In case of full-thickness mastectomy skin flap loss, deep vascular plexus present in the dermal bed of the underlying de-epithelialized skin paddle of the free flap converts an otherwise full-thickness wound to a partial-thickness wound. Our study demonstrates the self-epithelialization potential of the de-epithelialized dermal wound bed from the dermal appendages when exposed to air and in the presence of wound healing elements.